Language, Identity and Social Integration: Stories of Skilled Bangladeshi Immigrants in Canada - Shams, Shaila (Journal of the Canadian Association for Curriculum Studies, 2020)
This emerging ethnographic study aims to explore the impact of English language and learning on the settlement and social integration of skilled Bangladeshi immigrants in Canada. Though language is a significant factor in immigrants’ settlement, few researchers have explored the relationship between language and immigrants’ social integration, and even fewer have researched the impact of language in skilled immigrants’ settlement (Han, 2007; Gimpapa & Canagarajah, 2017). Canada is a popular destination for Bangladeshi skilled immigrants; however, they have remained largely ignored in the academic research and in the ethno-social milieu of Canada. Therefore, this study aims to explore how Bangladeshi skilled immigrants learn the English language, how they socialize using the language and what struggles they face in learning the language. The conceptual framework of the research is drawn from a poststructural understanding of language (Bourdieu, 1977, 1986) and sociocultural theory of learning (Block, 2013; Lave & Wenger, 1991; Ochs, 1991), and the research methodology is informed by critical theory and critical ethnographic sociolinguistic research (Heller et al., 2017). The significance of this research lies in exploring the role of language, access and participation in the settlement of the underrepresented Bangladeshi skilled immigrants in Canada and in reconceptualizing migrants’ language learning needs and scopes.